2017
DOI: 10.22630/pefim.2017.18.67.32
|View full text |Cite
|
Sign up to set email alerts
|

Analiza ESG spółek z indeksu RESPECT – podsumowanie badań

Abstract: This study is a summary of the research related to the ESG analysis of companies included in the RESPECT Index. The aim of the article is to make the comparative assessment of information obtained from two databases: ASSET4 ESG and Thomson Reuters Eikon and on the basis of this information make an analysis of the ESG results of companies from the RESPECT Index. The analysis is intended to answer the question whether the companies in the index are really those who fulfill at the highest level the requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…ESG scores from the ASSET4 ESG database are more favourable for companies. The researchers emphasise that the qualification of a company as one operating sustainably in its business practices, and its inclusion in the index of companies characterised as sustainable in running a business, should be unambiguous and should not raise doubts (Sikacz & Wołczek, 2017). In addition, the authors note another objectionable fact-the 10th edition of the RESPECT index under review included companies with very low ESG assessment scores.…”
Section: Literature Reviewmentioning
confidence: 99%
“…ESG scores from the ASSET4 ESG database are more favourable for companies. The researchers emphasise that the qualification of a company as one operating sustainably in its business practices, and its inclusion in the index of companies characterised as sustainable in running a business, should be unambiguous and should not raise doubts (Sikacz & Wołczek, 2017). In addition, the authors note another objectionable fact-the 10th edition of the RESPECT index under review included companies with very low ESG assessment scores.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, it can be concluded that the market perceives this kind of companies as more reliable, less risky and rewards them accordingly. However, there is no doubt that the importance of non-financial results will increase in the light of the investments made and strategic decisions (Sikacz & Wo czek, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%